Production of Anti-Recombinant Human Insulin Antibody and Validation by Indirect ELISA - Ambarsari, Christy; Suryadi, Herman; Yanuar, Arry (Indonesian Journal of Pharmaceutical Science and Technology, 2023)
Human insulin potential has become an interest and is important in maintaining the success of therapyin patients with the availability of chemical-based analytical methods, however, only a few have beenusing immunoassays. This study aimed to produce IgG polyclonal antibodies from rabbits immunizedwith 1 mg/mL rhINS subcutaneously and validated by indirect ELISA. Antibody was precipitated andfractioned on a HiTrap® Protein A HP column before being quantified with a UV spectrophotometerat λ 280 nm. The characterization was conducted by Dot Blot test on a BCIP-NBT substrate, as well asSDS-PAGE and Western Blot with polyacrylamide gel concentrations of 7.5% and 17.5%. Validationwas performed using solutions containing glycerol and m-cresol as matrices spiked with rhINS. Thelinearity test in the rhINS concentration range of 80.11-200.28 μg/mL (r = 0.99) showed the linearresult. The accuracy and precision obtained an average of 99.11%±5.01 and 3.91%, while the LODand LOQ were 22.05 μg/mL and 73.51 μg/mL, respectively. Human insulin was stable at 2-8oC for 24hours (α: 0.05, ANOVA). In conclusion, in-house produced IgG polyclonal antibodies and goat anti-IgG peroxidase conjugate can be used for routine testing of human insulin.